Pemanfaatan Minyak Jelantah sebagai Lilin Aroma Terapi untuk Meningkatkan Minat Berwirausaha Pemuda Muhammadiyah Desa Batu Belah - Dahlia, Agus; Qudsi, Rahma; Purnamawati, Neneng; Rahmatillah, Putri (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2024)
This service activity aims to increase the entrepreneurial interest of Muhammadiyah Youth members in Batu Belah Village, Kampar District, Kampar Regency, by utilizing community waste, namely used cooking oil which is disposed of in the surrounding environment. The method used is to provide training in processing used cooking oil into aromatherapy candles. From the training provided, it is hoped that it will create a new entrepreneur in the partner environment so that it can increase the income of its members.